Elaboración del estatuto orgánico funcional y manual de perfil de puestos por competencia para la Fundación Centro de Apoyo y Solidaridad “Alianza” - Párraga, Jhonny Francisco (2020)
The development of a functional organic status and handbook of position profile by competence in the Foundation Center for Support and Solidarity "Alliance", allowed to improve internal communication so that there is a higher performance with the control of work performance, as well it determined the type of degree of authority of the departments and their location at the hierarchical levels, becoming a support tool, which will be essential for the organization to effectively fulfill its mission, vision and objectives. Deductive, inductive, analytical and descriptive methods were used. In addition to techniques such as: observation, interview and survey. Drawing on the following tools: position description sheet, observation sheet, questionnaire, value chain, process map and vertical organization chart. All this helped to determine the positions, areas and units of work such as: legal advice; management unit; planning and monitoring; financial management unit; area of health; unity of human talent; social area and information and communication technology. It was also possible to define the specific competencies for the different jobs being the most important: management capacity, knowledge in law, ethics, humanism, proactive attitude, and empowerment. Synthesizing the development of the Functional Organic Statute of the Centre for Support and Solidarity Alliance foundation, it allowed to provide legal life, in addition to defining the lines of authority and responsibility, as well as the functional structure of the Foundation, which was represented through a value chain, process map, and vertical organization chart. While the design and elaboration of the competition position profile manual strengthened the administrative and functional management of the institution.